DIAGNOSIS AND TREATMENT OF HEMATOGENIC OSTEOMYELITIS - Berdiyarova Shokhida Shukurullaevna; Yusupova Nargiza Abdikodirovna; Ahadova Mahliyo Mukhtar qizi (Research Focus International Scientific Journal, 2023)
Inflammatory diseases of the skeleton are one of the most severe and common diseases of the musculoskeletal system in children and adolescents, including a large group of destructive bone lesions of various etiologies, united by the general term "osteomyelitis". At the same time, the clinical, laboratory and radiological picture of both infectious (specific granulomatous and nonspecific purulent) and non-infectious ("non-bacterial, abacterial") osteomyelitis may have a similar picture, which leads to inevitable diagnostic errors and, accordingly, the choice of erroneous treatment methods.